Pengalaman Perawat Dalam Memberikan Asuhan Keperawatan Pada Pasien Terinfeksi Covid - 19 - Tuti anggriani Utama; Sukmawati Sukmawati; Feni Eka Dianty (Universitas Mitra Indonesia, 2020)
Nurses as health workers have the most frequent contact with Covid-19 patients during nursing care. Anxiety, nurses' fear of the risk of contracting the Covid-19 virus can give birth to unprofessional attitudes and behaviors in providing nursing care to patients. This study aims to identify the experiences of nurses while caring for patients infected with Covid-19. Qualitative data were obtained through in-depth interviews with five nurses at a hospital in Bengkulu. The results of the study found four main themes, namely knowledge of Covid-19, nurse professionalism, nurses' feelings while caring for patients, and efforts to prevent transmission. The results of the study found four main themes, namely knowledge of Covid-19 care, nurses' motivation, the psychological condition of nurses while caring for patients, efforts to prevent transmission and the role of nurses in providing nursing care carried out by nurses to the families of Covid-19 patients. The results of this study concluded that the need for research on the Application of the Family-Centered Nursing Model to the Implementation of Family Health Duties in Prevention of Covid-19 Transmission.Key Words: Nurses, nursing care, Covid - 19.